End-of-life preferences of cardiac patients - Martin Gřiva; Jiří Šťastný; Jan Švancara; Martin Loučka; Veronika Belanová (University of Ostrava, 2018)
Aim: To address the wishes of patients with cardiovascular disease in relation to their end-of-life stage - an issue that has long been regarded taboo. Design: Cross-sectional study. Methods: After an initial interview, 127 patients completed an anonymous questionnaire: 86 patients (67.7%) hospitalized in a cardiology department, and 41 patients (32.3%) on follow-up at an outpatient clinic. The mean age was 67 ± 13 years; 60.6% were male; 51.7% were NYHA class III. Seventeen patients (13.4%) had an implantable cardioverter-defibrillator. Results: The patients most concerned about their future were those aged 65-79 years (p = 0.044); patients who felt they were not receiving sufficient information (p = 0.008); hospitalized patients (p < 0.001); or those with a known diagnosis of less than one month, or over one year (p = 0.038). Seventy-one patients (57.7%) would prefer to die at home, although this would mean receiving less health care than in hospital. Only 19 patients (15.4%) expressed a preference for extension of life over quality of life. Twenty-nine patients (23.6%) would contemplate having their cardioverter-defibrillator deactivated. 90.2% subjects considered it important for physicians to be interested in the views of patients regarding these issues. Conclusion: Despite the contrast with practice in some countries, most patients with cardiovascular disease would appreciate physicians being interested in their attitudes to the issue of end of life. An adequate level of information would help reduce patient concerns about their futures.